Tigliane Diterpene Esters from the Leaves of Croton tiglium. Issue 7 (July 2014) - Ren, Feng‐Xia; Ren, Feng‐Zhi; Yang, Yu; Yu, Neng‐Jiang; Zhang, Yang; Zhao, Yi‐Min
Abstract Three new tigliane‐type diterpene esters, 1–3 with unusual 7‐oxo‐5‐ene or 7‐hydroxy‐5‐ene moieties in their skeletons, were isolated from the leaves of Croton tiglium. Their structures were unambiguously elucidated on the basis of spectroscopic data.